2022
DOI: 10.5194/bg-19-1355-2022
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite regeneration in the oligotrophic Atlantic Ocean

Abstract: Abstract. The recycling of scarce nutrient resources in the sunlit open ocean is crucial to ecosystem function. Nitrification directs ammonium (NH4+) derived from organic matter decomposition towards the regeneration of nitrate (NO3-), an important resource for photosynthetic primary producers. However, the technical challenge of making nitrification rate measurements in oligotrophic conditions combined with the remote nature of these environments means that data availability, and the understanding that provid… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…There is no clear latitudinal trend in the ammonia oxidation rates. In contrast, Clark et al (2022) found higher ammonia oxidation rates in the Southern Hemisphere along the north-south transect in the Atlantic Ocean. This latitudinal pattern is hypothesized to be explained by the difference in the supply of dissolved organic nitrogen (DON) by lateral transport into the gyre interior from the eastern boundary upwelling (Clark et al, 2022).…”
Section: Distribution Of Ammonia Oxidationmentioning
confidence: 58%
See 3 more Smart Citations
“…There is no clear latitudinal trend in the ammonia oxidation rates. In contrast, Clark et al (2022) found higher ammonia oxidation rates in the Southern Hemisphere along the north-south transect in the Atlantic Ocean. This latitudinal pattern is hypothesized to be explained by the difference in the supply of dissolved organic nitrogen (DON) by lateral transport into the gyre interior from the eastern boundary upwelling (Clark et al, 2022).…”
Section: Distribution Of Ammonia Oxidationmentioning
confidence: 58%
“…In contrast, Clark et al (2022) found higher ammonia oxidation rates in the Southern Hemisphere along the north-south transect in the Atlantic Ocean. This latitudinal pattern is hypothesized to be explained by the difference in the supply of dissolved organic nitrogen (DON) by lateral transport into the gyre interior from the eastern boundary upwelling (Clark et al, 2022). The stimulation of ammonia oxidation rates by a lateral DON supply has also been observed in the western Pacific (Xu et al, 2018).…”
Section: Distribution Of Ammonia Oxidationmentioning
confidence: 58%
See 2 more Smart Citations
“…the NSTG will contain some waters from the deep Mediterranean outflow, whilst the SSTG is traversed by Agulhas Rings carrying Indian Ocean water (Nencioli et al, 2018). There are also hemispheric differences in the availability of dissolved organic nitrogen (Clark et al, 2022). Smyth et al (2017) also illustrate the differences in seasonal forcing for these two gyres.…”
Section: Cruise Data From the Atlantic Meridional Transect Programmementioning
confidence: 99%